ETHNOMEDICAL USES OF MADHUCA LONGIFOLIA – A REVIEW: Life Science-Microbiology - K.N. AKSHATHA; MURTHY, S. MAHADEVA; N. LAKSHMIDEVI (International Journal of Life Science and Pharma Research, 2013)
Madhuca longifolia commonly called as mahua is such a kind of tree involved in day to day activity of tribal people. It belongs to the family Sapotaceae, an important economic tree growing throughout India. The Mahua tree is medium sized to large deciduous tree, usually with a short bole and a large rounded crown. Ethnomedical uses say to possess significant antipyretic, hepatoprotective, anti-inflammatory, analgesic, antitumour, antiprogestational, antiestrogenic and wound healing activity. Traditionally M. longifolia bark is used in rheumatism, ulcers, bleedings and tonsillitis. The present review contains the various ethnomedical and traditional uses of bark and leaves of M. longifolia